The characteristics of invasive cardiac lipoma: case report and literature review - Zhu, Xiliang; Cheng, Zhaoyun; Wang, Sheng; Chen, Xianjie; Lu, Guoqing; Li, Xiaoyang (Frontiers in Cardiovascular Medicine, 2023)
Invasive cardiac lipoma is a rare type of primary cardiac tumor that is composed of adipose tissue but infiltrating the adjacent structures. It is a benign tumor that can cause significant morbidity and mortality due to its size and location within the heart. We describe a giant invasive intracardiac lipoma across atrial wall extending to the ascending aorta and the superior vena cava. This review will provide an overview of invasive cardiac lipoma, including its clinical presentation, diagnosis, and management.